Second-degree Price Discrimination and Inter-group Effects in Airline Routes between European Cities - Marco Alderighi; Alessandro Cento; Peter Nijkamp; Piet Rietveld (Tinbergen Institute, 2011)
This paper presents a model of second-degree price discrimination and inter-group effects to describe the full-service pricing behaviour in the passenger aviation market. Consumer heterogeneity is assumed on both a horizontal and a vertical dimension, while various distinct market structures, some of which include low-cost carriers (LCCs), are considered. In the theoretical model framework, we derive that the rivalry between full-service carriers (FSCs) reduces fare differences between the business and leisure segments. Furthermore, the presence of LCCs increases fare gaps between leisure and business travellers, and it also induces FSCs to decrease fares in the leisure segment and eventually to increase them in the business one. This last outcome emerges from a change in passenger arrangements caused by inter-group effects. In our empirical analysis, we use data on published airfares of Lufthansa, British Airways, KLM and Alitalia for the main city-pairs from Italy to Germany, the UK and the Netherlands. Our results show that the empirical results provide support for our theoretical propositions.
urn:NBN:nl:ui:31-1871/38524
Keywords: L1; L93; D4; 330; Passenger aviation market; Price discrimination; Low-cost carriers; Passagierluftfahrt; Preisdifferenzierung; Luftverkehrsgesellschaft; Europa